Pengaruh Penerapan Metode Pembelajaran Fisika Berbasis Eksperimen Virtual Terhadap Motivasi Dan Hasil Belajar Fisika Siswa Kelas X MAN 2 Mataram Tahun Ajaran 2014/2015 - Muthmainnah Muthmainnah; Joni Rokhmat; Jannatin 'Ardhuha (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This research aimed to know the effect of physics learning method with virtual experiment on motivation and physics learning result of 10th grade students of MAN 2 Mataram in academic year of 2014/2015. This experiment employed posttest only control group design. Samples were taken by using purposive sampling technique. X 3 class was chosen as experiment class and X 5 as control class. The result showed that motivation and learning results of experiment class students mean score were 78.75 and 78.20, respectively, while the motivation and learning results of control class students mean score were 68.29 and 64.67. The motivation data of both classes were homogeneous. On the other hand, the learning results of both classes were not homogeneous. Both data were analyzed by using t-test. It was obtained that tcount score were 6.10 and 5.18 for motivation and learning results, respectively, with ttabel score were 1.99 and 2.04 at significant rate of 5%. The tcount was greater than ttabel, which meant there was difference between the students who were got the physics learning method with virtual experiment and the conventional one. It can be concluded that physics learning method with virtual experiment affected motivation and physics learning results.ÃÂ